Pengembangan Media Pembelajaran Video Berbasis Sparkol Videoscribe pada Materi IPA Tata Surya Kelas VI Sekolah Dasar - Sekar Diah Ayu Dinuli; A.F. Suryaning Ati MZ; Humairah Humairah (Jurnal Tematik, 2026)
This study aims to develop a valid and effective video-based learning media using Sparkol Videoscribe for teaching the Solar System topic in the sixth-grade science curriculum at SD Negeri 1 Lawak. The research employed a 4D development model (Define, Design, Develop, Disseminate). Data were collected using expert validation sheets, student response questionnaires, and student activity observation forms. The validation results showed that the developed media was highly valid, with media expert validation scoring 96%, design expert validation scoring 96%, and content expert validation scoring 96.5%. Furthermore, the student response instrument achieved a score of 94.5%, and the student activity instrument scored 95.5%. The media was also considered effective based on students’ active engagement and positive feedback during the learning process. Therefore, Sparkol Videoscribe-based learning media is deemed appropriate as an alternative instructional tool in science learning, particularly for abstract topics such as the Solar System.